Implementation of Minister of Finance Regulation 212 of 2022 on Village Funding in Togolobe Village, Hiri Island District, Ternate City - Aji Deni; Irwan Bakar; Thamrin Husain; Saiful Deni; Darwin Abd Radjak (Jurnal Ekonomi dan Bisnis Digital, 2024)
The funding for community empowerment on Hiri Island, an isolated administrative district of Ternate City, requires attention to support the development of the island communities. The objective of this study is to assess the application Minister of Finance Regulation in the allocation of funds in 2023 year. This study used a qualitative methodology to examine Edward III's concept of policy implementation. With the qualitative methodology, the studies finding that the allocation of funds has proven to be highly effective in empowering the community. The communication, allocation of resources, performance of staff, and work quality of Hiri sub-district employees are highly professional. Their team demonstrate a transparent disposition, collaboration is commendable, including the effective mechanism for controlling policies at the lower levels.